Miskonsepsi Pengerjaan Operasi Deret Matematika di PGMI 3 UIN Sumatera Utara - Handini, Nurul; Wandini, Rora Rizki (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This article identifies various types of misconceptions experienced by UIN North Sumatra students when they solve problems related to mathematical series operations material, as well as to understand the causes of misconceptions among students in this context. This research uses qualitative methods in the form of descriptive research with the data collection method used is a test to identify misconceptions that students may experience. The results of the analysis show that students still often experience misconceptions when solving problems related to geometric series operations. The types of misconceptions identified among students include translation misconceptions, concept misconceptions, sign misconceptions, and systematic misconceptions. The causes of misconceptions can generally be attributed to students, with several factors at play. Misconceptions can occur due to wrong preconceptions that students previously had, incomplete or wrong reasoning in solving problems, and students' abilities that may still be lacking in understanding the material.